2010
DOI: 10.1183/09031936.00022909
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled drugs as risk factors for community-acquired pneumonia

Abstract: The effect of inhaled drugs in community-acquired pneumonia (CAP) is unclear. This case-control study was designed to determine whether inhaled drugs were risk factors for CAP.All incident cases of confirmed CAP that occurred over 1 yr in patients with chronic bronchitis (CB), chronic obstructive pulmonary disease (COPD) or asthma were included, as well as CB, COPD and asthma controls. Risk factors for CAP and inhaled treatment were recorded during a personal interview.An effect of inhaled drugs on the risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 42 publications
2
37
0
2
Order By: Relevance
“…In some studies [8,23] , an effect of inhaled drugs on the risk of CAP was observed in COPD and asthma patients after adjusting for the effect of other respiratory diseases (and their concomitant treatments) and other nonrespiratory risk factors for CAP, including vaccines [8] . There are 8 studies assessing the effect of inhalation therapy on the risk of CAP.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies [8,23] , an effect of inhaled drugs on the risk of CAP was observed in COPD and asthma patients after adjusting for the effect of other respiratory diseases (and their concomitant treatments) and other nonrespiratory risk factors for CAP, including vaccines [8] . There are 8 studies assessing the effect of inhalation therapy on the risk of CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Congestive heart failure was based on the use of diuretics in combination with digitalis. Besides co-morbidities also the use of morphine, non-steroidal antiinflammatory drugs, antiplatelet drugs, and corticosteroids was assessed because these types of treatment have been associated with risk of pneumonia in other studies [1,19]. For all drugs, drug use was defined as two or more prescriptions/dispenses in the 182 days before the index date.…”
Section: Potential Confoundersmentioning
confidence: 99%
“…We evaluated use of nonsteroidal antiinflammatory drugs (NSAIDs), antidiabetics (as a proxy for diabetes mellitus (DM)), opiates, antiplatelet therapy, inhalation medication (as a proxy for chronic obstructive pulmonary disease (COPD) or asthma) and digoxin plus diuretics (as a proxy for congestive heart failure (CHF)). Besides these, inhaled corticosteroids and anticholinergics were also evaluated as separate potential confounders [21,22]. Prescriptions for oral corticosteroids during the month prior to the index date and for antibiotics during the 6 months prior to the the index date were also assessed.…”
Section: Potential Confoundersmentioning
confidence: 99%